Pengaruh Kepuasan Kerja Dan Komitmen Karyawan Terhadap Turnover Intention Pada Karyawan Bagian Produksi PT. Majoin Coness Indonesia Di Malang - Shofiatul Khasanah; Muhammad Ridwan Basalamah; Nurhidayah Nurhidayah (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This research was conducted with the aim of knowing the effect of job satisfaction and employee commitment on turnover intention in employees of the production division of PT. Majoin Coness Indonesia which is located in Malang. The instrument used in this study was a questionnaire consisting of a number of questions regarding job satisfaction, turnover intention, and employee commitment. The high rate of employee exit from the company will lead to higher costs incurred by the company for recruiting employees and retraining costs. This research was conducted with the number of respondents taken as many as 251 employees using the census method. Data collection is done by distributing questionnaires. The data analysis technique that will be used in this research is path analysis. Based on the results of the analysis, it was found that job satisfaction has a positive and significant effect on organizational commitment. Job satisfaction partially significant effect on turnover intention. Employee commitment partially significant effect on turnover intention. There is a simultaneous significant effect of the independent variable in the form of Job Satisfaction and Employee Commitment to the dependent variable in the form of Turnover Intention. Keywords: Job Satisfaction, Turnover Intention, Employee Commitment.